2014
DOI: 10.1194/jlr.m053389
|View full text |Cite
|
Sign up to set email alerts
|

Micron-scale assessment of molecular lipid organization in human stratum corneum using microprobe X-ray diffraction

Abstract: This article is available online at http://www.jlr.org complex and specifi c architecture of the inter-corneocyte lipid matrix ( 2 ) composed of a mixture of ceramides, cholesterol, and long-chain fatty acids. Ultrastructural studies, using electron microscopy and diffraction techniques, have revealed that these lipids are organized in stacked bilayers that are predominantly parallel to the skin surface ( 3-5 ). Part of the lipids is covalently bound to the corneocytes whereas another part represents the "free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 29 publications
4
40
1
Order By: Relevance
“…5,6,9 Doucet et al estimated that the relative abundance of lipids in organized phases with hexagonal and orthorhombic hydrocarbon packing structures is 20 ± 10% based on WAXD profiles. 13 Hatta et al also concluded that more than 50% of the total intercellular lipids in SC exist in a disorganized liquid state from WAXD measurements on ethanol treated hairless mouse SC. 14 From a solid-state NMR study, Björklund et al proposed that the majority of the intercellular lipids are rigid at 32°C, but they coexist with a small pool of mobile disordered lipids that might be in a disorganized liquid crystalline phase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…5,6,9 Doucet et al estimated that the relative abundance of lipids in organized phases with hexagonal and orthorhombic hydrocarbon packing structures is 20 ± 10% based on WAXD profiles. 13 Hatta et al also concluded that more than 50% of the total intercellular lipids in SC exist in a disorganized liquid state from WAXD measurements on ethanol treated hairless mouse SC. 14 From a solid-state NMR study, Björklund et al proposed that the majority of the intercellular lipids are rigid at 32°C, but they coexist with a small pool of mobile disordered lipids that might be in a disorganized liquid crystalline phase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many authors have proposed from X‐ray diffraction measurements that a disorganized liquid crystalline phase exists in SC . Doucet et al estimated that the relative abundance of lipids in organized phases with hexagonal and orthorhombic hydrocarbon packing structures is 20 ± 10% based on WAXD profiles . Hatta et al also concluded that more than 50% of the total intercellular lipids in SC exist in a disorganized liquid state from WAXD measurements on ethanol treated hairless mouse SC .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intercellular lipids (ICL) of the lipid matrix are organized in the form of a classical membrane and their orthorhombic lateral organization represents a highly ordered and very densely packed structure, which is notpermeable for the majority of the non-destructive substances [2][3][4]. The depth distribution of the lateral organization of ICL is non-homogeneous in the SC, showing a prevalence of orthorhombic over hexagonal ordering in the intermediate SC depths measured in vitro [5,6]. The prevalence of the orthorhombic lateral organization in the SC maintains the skin barrier…”
mentioning
confidence: 99%